FILLING IN MANDIBULAR CONTOUR WITH HYALURONIC ACID: CLINICAL CASE REPORT - Mara Xavier de Oliveira, Luísa; Cristina Maurício Milagre Diniz, Helen (Health and Society, 2022)
The shape of the jawline has a profound effect on an individual’s appearance and is an area of attention for many people looking for aesthetic procedures. Hyaluronic acid is one of the best fillers used today. Fillers at the angle of the jaw widen or augmentation the angle and make a sharp contour of the posterior part of the jawline. In the chin, fillers improve projection and the appearance of the fat deposit submental. Contouring is a procedure with satisfactory results desired for men to make the contour more designed in the mandibular area. The aim of this study is to present a clinical case the filler’s hyaluronic acid in the jawline and chin of the male face, in order to improve the characteristics inherent to the male facial contour. The methods used high G prime hyaluronic acid fillers to provide mandibular volumization, projection and augmentation of the chin. Two sessions were performed, totaling 8 fillers injection. The pictures the before and after is possible to observe the lower third of the face more augmented, at 45º the mandibular contour including ascending ramus, angle and body more marked and at 90º the projection of the chin. By comparing the photographs of before and after the treatment, there was a change in the facial pattern and the balance of maxillomandibular relationships was achieved together with aesthetic satisfaction.